Flow and performance: a quantitative study of elicitation modeling in a piano performance perspective - Li, Junrui; Xu, Ying; Wang, Xiaoyu; Yuan, Xinran; Liu, Shilin; Li, Meihui; Ren, Xiubo; Yang, Dan; Liu, Siqi; Jiang, Zhenxu; Gou, Qiaoqiao; Yang, Miaomiao; et al. (Frontiers in Psychology, 2024)
Flow, defined as a heightened state of consciousness characterized by intense concentration during an activity, is influenced primarily by the perceived challenge and the dynamic equilibrium of skills. This investigation focuses on the patterns of flow state attainment and its elicitation mechanisms within the context of piano performance among Chinese music college students. Our study establishes a framework for accessing the flow, utilizing quantitative data from music ontology to gauge the level of challenge and the level of music acquisition to assess skills. Additionally, we integrate external factors such as music culture heterogeneity and demographic variables to elucidate the causes and moderating effects of flow on piano performance. The findings reveal a positive correlation between flow and performance, with the model of challenge and skill induction partially explaining these results. Notably, melodic Shannon Entropy emerges as a potential indicator of challenge, suggesting its relevance in future studies on flow. This research provides multidimensional insights into the interplay between performance and flow in piano performance, guiding future investigations to explore the musical quantitative perspective more deeply.